VARIETY OF STAPLE FOODS: Perceptions of Indonesian Society on Other Staple Foods of Rice - Rusdi, Muhammad (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
The thing that needs to be understood is that staple food is considered a principle in meeting the needs of life. So that there is an urge within or lust that cannot be ruled out. It's different with complementary foods which are perceived as an option, so people can ignore them, because there are no consequences for the body's needs. Similar to Indonesians, rice is a staple food that cannot be replaced with other staple foods, while Indonesia itself produces many other staple foods such as corn, wheat, sago and tubers. This becomes interesting to study, and find out about the various factors that cause differences in perceptions of staple foods. The scientific method used to explain this phenomenon is quantitative with linear regression analysis. This research was conducted in Jakarta with a total of 150 respondents who were taken randomly. Disclosure of research objectives focuses on three statistical tests, namely partial, simultaneous and contribution hypothesis testing. The results of the study show that self-motivation or lust for rice is a strong factor, why Indonesians prefer to eat rice over other staple foods. This also explains that the public's perception of non-rice staple foods is a desire, for example encouragement or motivation for health.